Perbandingan Pelaksanaan Pidana Mati Dalam KUHP 1946 dan Nomor 1 Tahun 2023 - HTPA, Anggriyani; Carera, Famelinda; Falihah, Fauziyyah Nur; Santoso, Yulika Putri; Anwar, Muhammad Syaiful (Fakultas Hukum Universitas Islam Batik Surakarta, 2024)
The purpose of writing this journal is to discuss and explain the differences in the principle oflegality contained in the Criminal Code of 1946 with number 1 of 2003 on the implementationof the death penalty. In analyzing this research, the method used is normative juridical withtwo approaches, namely the first using a (statute approach) where the approach is to study thelaws and regulations of a case that has been studied based on the law. Second, namely(conceptual approach) a view of legal concepts, doctrines, and principles regarding legaldevelopment. So with this, it can be seen the differences contained in the Criminal Code of1946 with number 1 of 2003 concerning the death penalty and its usefulness as a guideline indeciding the death penalty.